Hitler's Forgotten Ally - Deletant, D. author. aut Link
X, 379 p.
Keywords: This book is the first complete study in English of Antonescu's part in the Second World War. Antonescu was a major ally of Hitler and Romania fielded the third largest Axis army, joined the Tripartite Pact in November 1940 as a sovereign state and participated in the attack on the Soviet Union of 22 June 1941 as an equal partner of Germany.